Herland and Charlotte Perkin Gilman’s Utopian Social Vision of Women And Society - Shahizah Ismail Hamdan; Ravichandran Vengadasamy (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2006)
Charlotte Perkins Gilman’s novel, Herland, is regarded by many as the pioneering feminist utopian novel. Authored in 1915 (but published as a monograph only in 1978), Herland is intended as a social critique, and as a sociological theorist, Gilman sees herself as a change agent for a better social life for women especially, as well as society in general. Like other intellectuals at the turn of the 20th century, Gilman struggled to theorise her social vision, whilst simultaneously placing great efforts at promoting her vision in a package that is attractive to the masses. By self-consciously distancing herself from the intellectuals of her time, she crafted her works as endeavours at transforming society. With the utopian novel as her genre of choice, Gilman provides readers with a deeper sense of understanding of the ills of a society that subscribes to and is fixated with masculinity. As such, it is the contention of this paper to discuss Gilman’s second novel, Herland as a feminist utopian novel critiquing some aspects of culture Gilman describes as androcentric and to briefly link the images portrayed by Gilman in Herland to the Jungian theory of archetypes with some reference to female archetypal images.